Hipster Porn Queer Masculinities and Affective Sexualities in the Fanzine Butt - Rehberg, Peter (2022)
Hipster Porn examines models of gay hipster masculinity through the lens of the gay fanzine Butt. The book reconstructs an important chapter of recent gay and queer history in order to make sense of the cultural shifts of the last 20 years in the contemporary gay world.Butt exemplifies the changing nature of gay contemporary masculinity as it marked the beginning of a new era of queer fanzines such as They Shoot Homos Don't They?, Kink, Kaiserin, and Meat reflecting a specific cosmopolitan gay lifestyle in the West of the 2000s. The new forms of masculinity and sexuality demanded new ways of thinking about gender and desire. Hipster Porn takes the aesthetics of Butt to find a way of critiquing and rearticulating key concepts from gender, queer and affect theory, and delivers new accounts of subjectivity and sociality as they apply to queer media culture. This book is suitable for researchers in gender studies, queer and masculinity studies, cultural studies, media studies, and sociology.